2016
DOI: 10.1128/aem.03989-15
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Aerosol-Deposited Yersinia pestis from Indoor Surfaces To Determine Bacterial Environmental Decay

Abstract: Public health and decontamination decisions following an event that causes indoor contamination with a biological agent require knowledge of the environmental persistence of the agent. The goals of this study were to develop methods for experimentally depositing bacteria onto indoor surfaces via aerosol, evaluate methods for sampling and enumerating the agent on surfaces, and use these methods to determine bacterial surface decay. A specialized aerosol deposition chamber was constructed, and methods were estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…All known strains of Yersinia are non-spore forming and for some, especially virulent strains, an ability to survive in aquatic environments and in humidified soils (up to 280 days) is already known [ 41 – 43 ]. It was shown that the virulent Yersinia pestis strain CO92 can persist after short term exposure (up to one hour) on different dry surfaces like glass and steel [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…All known strains of Yersinia are non-spore forming and for some, especially virulent strains, an ability to survive in aquatic environments and in humidified soils (up to 280 days) is already known [ 41 – 43 ]. It was shown that the virulent Yersinia pestis strain CO92 can persist after short term exposure (up to one hour) on different dry surfaces like glass and steel [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, bacteria in aqueous solution can be transported to a solid surface as aerosols [17], [18] or sedimentation [19], [20]. Under static conditions, bacterial mass transport is mostly due to sedimentation while under dynamic conditions, the mass transport is a combination of sedimentation, convection, and diffusion [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined the persistence (or natural attenuation) of nonspore‐forming bacteria (King et al ; Aune et al ; Calfee and Wendling ; USEPA ; Gut et al ) and viral select agents (Berendt and Dorsey ; Lai et al ; Graiver et al ; Sagripanti et al ; Yamamoto et al ; Pyankov et al ; Verreault et al ; Brown et al ) and have shown the ability of these agents to persist in various matrices or altered states (lyophilization) for months, however, many of these studies did not detail the effects when applied to common building fomites.…”
Section: Introductionmentioning
confidence: 99%